THE IMPORTANCE OF LEARNING ENGLISH IN THE MODERN WORLD - Isroilova Gulruh (TADQIQOTLAR, 2026)
Abstract. In the modern globalized world, the English language plays a crucial role as a primary means of international communication. It is widely used in education, science,  business,  technology,  and  diplomacy,  making  it  an  essential  skill  for individuals  seeking  academic  and  professional  success.  Learning  English  enables people to access a vast amount of information, participate in global discussions, and build cross-cultural connections. Moreover, proficiency in English enhances career opportunities,  promotes  cultural  exchange,  and  supports personal  development. As digitalization and globalization continue to expand, the importance of learning English becomes increasingly significant, positioning it as a key tool for integration into the modern world.